Private versus Third Sector Project Evaluation Techniques; Can Private Sector PET be used to improve the Third Sector PET? - Akhtar, Farheen (2018)
Over the last few years, the role of NGOs has become integral to international development. There is a reliance on the third sector acting as intermediary between donors and beneficiaries. The rise of investment in third sector organisations has led to an increased demand of accountability mechanisms justifying their strategic decisions and resource allocation. This study aims to assess 1) the viability of third sector PETs practiced in Pakistan, 2) investigate private and third sector PETs against a set criterion, and 3) examine whether private sector PETs can be utilised to improve third sector PETs. Data for the study was gathered through method triangulation; using qualitative interviews and documentary analysis, a matrix method of literature review was conducted on five PETs from the two sectors. Results of the primary research in Pakistani NGO has been organised into four themes; evaluation purpose, organisational internal control mechanisms, donor requirements and stakeholder participation. The first three themes are set as criterion against whom the assessment models are evaluated. Findings and analysis of the study are interpreted through a matrix literature review, to address the evaluative shortcomings NGOs face in Pakistan. The results show significant disparities in existing literature and actual practices of PETs in NGOs. While the literature is miles ahead in solving limitations faced by NGOs in project evaluation techniques, in practice the research found NGOs face assessment problems that are more pervasive than PETs. The study further concludes; although private sectors practices are not fully applicable to third sector, they can be adopted to improve aspects of NGO assessments by learning lessons of technological integration, embedding internal control mechanisms and providing capacity building trainings for effectively practicing evaluation tools.